Penerapan Metode Permainan Tradisional “Engkle” Untuk Meningkatkan Motivasi Belajar Siswa Kelas 2 SDN Bojong Kacor 03 Pada Materi Satuan Panjang - Nurlaila, Anisa; Nurishlah, Laesti; Yudiyanto, Mohamad; Samadi, Mochammad Ramdan (Prodi PGMI STAI Sabili Bandung, 2024)
This study concentrates on implementing the traditional Engkle game method to enhance learning motivation among second-grade students at SDN Bojong Kacor 3 Bandung, aiming to leverage game elements in mathematics instruction on the topic of length units. The choice of this topic is justified by the potential of game-based methods to serve as an effective strategy for increasing student engagement and motivation, particularly in mathematics, which is often perceived as monotonous by children. The research employs a qualitative classroom action research model, involving the preparation of teaching tools and materials, and the planning of activities across two cycles, which includes group arrangements and modifications to task execution methods. The findings indicate improvements in student motivation across all indicators: control and autonomy (81%), engagement (89%), task persistence (80%), and learning satisfaction (87%). This research underscores the efficacy of the Engkle game method in bolstering student motivation and involvement in mathematics education.